From SWEETBACK to SUPER FLY : Race and Film Audiences in Chicago's Loop - Butters, Gerald R., 1961- (Book collections on Project MUSE., 2015)
Racial politics and capitalism found a way to blend together in 1970s Chicago in the form of movie theaters targeted specifically toward African Americans. In From Sweetback to Super Fly, Gerald Buttersexamines the movie theaters in Chicago's Loop that became, as he describes them, "black spaces" during the early 1970s with theater managers making an effort to gear their showings toward the African American community by using black-themed and blaxploitation films. Butters covers the wide range of issues that influenced the theaters, from changing racial patterns to the increasingly decrepit state of Chicago's inner city and the pressure on businesses and politicians alike to breathe life into the dying area. Through his extensive research, Butters provides an in-depth look at this phenomenon, delving into an area that has not previously been explored. His close examination of how black-themed films were marketed and how theaters showing these films tried to draw in crowds sheds light on race issues both from an industrial standpoint on the side of the theaters and movie producers, as well as from a cultural standpoint on the side of the moviegoers and the city of Chicago as a whole. Butters provides a wealth of information on a very interesting yet underexamined part of history, making From Sweetback to Super Fly a supremely enjoyable and informative book.